MODEL PERENCANAAN PENGEMBANGAN PROGRAM SEKOLAH/MADRASAH BERBASIS ANALISIS KEBUTUHAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Laililrizqi, Lyra; Hamam Burhanuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Planning for the development of madrasah school programs is a strategic element in efforts to improve the quality of education in a sustainable manner. However, in practice, planning is often still administrative and not yet fully based on real-world needs analysis on the ground. This study aims to examine the planning model for the development of school/madrasah programs based on needs analysis as well as its implementation and evaluation strategies in improving the quality of education. The method used is library research with a qualitative descriptive approach through the analysis of various relevant scientific literature sources. The results of the study show that effective program planning must begin with a data-based needs analysis, followed by the formulation of adaptive goals, the preparation of contextual program designs, and the implementation that is carried out in stages. In addition, continuous monitoring and evaluation are important components in ensuring the achievement of program objectives. This study offers a conceptual model in the form of a need-based adaptive planning development cycle that emphasizes the integration between continuous planning, implementation, evaluation, and follow-up. The success of the implementation of the model is influenced by various factors, such as the leadership of the principal, teacher competence, the availability of infrastructure, school culture, as well as community participation and policy support. Thus, adaptive and sustainable needs analysis-based planning can increase the effectiveness of school programs and contribute to improving the quality of education optimally.